Can-do descriptors - realigning english language curriculum at higher education institution to CEFR / Erda Wati Bakar - Bakar, Erda Wati (Universiti Teknologi MARA Shah Alam, 2020)
The Common European Framework of Reference for Language (CEFR) has become the standard used to describe and evaluate students' command of a second or foreign language. It is an internationally acknowledged standard language proficiency framework which many countries have adopted such as China, Thailand, Japan and Taiwan. Malaysia Ministry of Education is aware and realise the need for the current English language curriculum to be validated as to reach the international standard as prescribed by the CEFR. The implementation of CEFR has begun at primary and secondary level since 2017 and now higher education institutions are urged to align their English Language Curriculum to CEFR as part of preparation in receiving students who have been taught using CEFR-aligned curriculum at schools by year 2022. This critical reflection article elucidates the meticulous processes that we have embarked on in re-aligning our English Language Curriculum to the standard and requirements of CEFR. The paper concludes with a remark that the alignment of the English curriculum at the university needs full support from the management in ensuring that all the stakeholders are fully prepared, informed and familiar with the framework.